2009
DOI: 10.1103/physrevlett.102.203601
|View full text |Cite
|
Sign up to set email alerts
|

Memory for Light as a Quantum Process

Abstract: We report complete characterization of an optical memory based on electromagnetically induced transparency. We recover the superoperator associated with the memory, under two different working conditions, by means of a quantum process tomography technique that involves storage of coherent states and their characterization upon retrieval. In this way, we can predict the quantum state retrieved from the memory for any input, for example, the squeezed vacuum or the Fock state. We employ the acquired superoperator… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 28 publications
1
67
0
2
Order By: Relevance
“…With a more careful analysis of the speed of convergence in (9), it can be shown that the weak LAN can be upgraded to the strong version described by (5) and (6) [20].…”
Section: Local Asymptotic Normality For Quantum Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…With a more careful analysis of the speed of convergence in (9), it can be shown that the weak LAN can be upgraded to the strong version described by (5) and (6) [20].…”
Section: Local Asymptotic Normality For Quantum Statesmentioning
confidence: 99%
“…Recently, statistical inference has become an indispensable tool in quantum engineering tasks such as state preparation [5,6] , precision metrology [7,8], quantum process tomography [9,10], state transfer and teleportation [11,12], continuous variables tomography [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…This type of "quantum process tomography" was performed by Lobino et al using single mode coherent states. 20 A generic measurement system would be able to extend these results to multimode states.…”
Section: Measuring Stored Quantum Statesmentioning
confidence: 99%
“…So far, successful demonstrations of quantum light storage have been used in atomic vapor [4], doped solid [5], and quantum cavity system [6,7]. Equally exciting is the possibility that these results will lead to useful applications in the fields of telecommunications and optical buffer [8]. There are several possible techniques of implementing quantum light memory such as electromagnetically induced transparency (EIT) [9], coherent population oscillation (CPO) [10], Raman and Brillouin amplification [11], among others [12].…”
Section: Introductionmentioning
confidence: 99%